Numerical Analysis of Parameters of the Radiant Heating System with Radiating Panels - Redko A.A.; Kulikova N.V.; Burda Yu.A.; Pavlovsky S.V.; Redko O.F.; Pivnenko Yu.A. (Problems of the Regional Energetics, 2020)
The main goal of the work is to study radiation and convection heat-exchange in a closed volume of a panel radiator to assess the possibility of transferring short-wave radiation in the working area to a comfortable long-wave one. The goals have been achieved through the use of a mathematical model of three-dimensional unsteady flow and complex heat exchange in a radiant heating system, in which the system of Reynolds-averaged Navier – Stokes equations is added, supplemented by the radiative transfer equation. The effect of the shape and size of the panel, surface material and the presence of thermal insulation has been numerically investigated. It has been found that the arrangement of radiating panels reduces the surface temperature to 450–500ºC, but the increase in the surface area of the radiator provides a more uniform radiation intensity over the area being heated, not exceeding the permissible sanitary and hygienic requirements. The most important results are the creation of a more uniform radiation flux density when placing additional panels around a high-temperature radiator and the conversion of short-wave radiation in the working area to a comfortable long-wave one. The significance of the obtained results consists in the fact that the results of these studies can be put into practice in the design and installation of radiant heating systems for various buildings. The results obtained in the work show the promise of further theoretical and experimental studies on subjects related to the optimization of radiant heating system parameters for industrial and civil buildings.